Far-red fluorescent genetically encoded calcium ion indicators - Rochelin Dalangin; Bill Z. Jia; Yitong Qi; Abhi Aggarwal; Kenryo Sakoi; Mikhail Drobizhev; Rosana S. Molina; Ronak Patel; Ahmed S. Abdelfattah; Jihong Zheng; Daniel Reep; Jeremy P. Hasseman; et al. (Nature Communications)
Abstract Genetically encoded calcium ion (Ca2+) indicators (GECIs) are widely-used molecular tools for functional imaging of Ca2+ dynamics and neuronal activities with single-cell resolution. Here we report the design and development of two far-red fluorescent GECIs, FR-GECO1a and FR-GECO1c, based on the monomeric far-red fluorescent proteins mKelly1 and mKelly2. FR-GECOs have excitation and emission maxima at ~596 nm and ~644 nm, respectively, display large responses to Ca2+ in vitro (ΔF/F 0 = 6 for FR-GECO1a, 18 for FR-GECO1c), are bright under both one-photon and two-photon illumination, and have high affinities (apparent K d = 29 nM for FR-GECO1a, 83 nM for FR-GECO1c) for Ca2+. FR-GECOs offer sensitive and fast detection of single action potentials in neurons, and enable in vivo all-optical manipulation and measurement of cellular activities in combination with optogenetic actuators.